Criminal Law Aspects of Assisted Human Reproduction in Serbia - Samardžić, Stefan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Numerous shortcomings of the Law on Infertility Treatment by Biomedically Assisted Fertilization culminate in provisions defining criminal offences. A question is raised regarding the possibility and results of the application of such criminal provisions due to the legislative technique used in the process of their creation, language, qualified forms of the offences, span of criminal sanctions, as well as having in mind the overlapping of such criminal offences with some of the misdemeanors punishable by the same Law. A possibility to provide for a criminal law protection in this highly sensitive area is put into question due to a very courageous action of the legislator reflected in the attempt to introduce criminal offences, punishable by long prison sentences.